Verification of the effect of adding nano-silicon oxide on the quality of friction stirs welding of AC-51300 aluminum Nano Composite - Mamoon A A Al-Jaafari (Peerian Journals Publishing, 2022)
This work aims to study the addition of different proportions of silicon oxide to aluminum alloys that are difficult to weld, and to show the results obtained to increase the strength and quality of the weld joint using friction stirs welding
Keywords: friction stirs welding; AC-51300 aluminum; silicon oxide; Nano Composite